Every Cloud has a Silver Lining: On the Relation between Bank-Affiliated Asset Manager Bias and Mutual Fund Fees - Enrico Miersch; Nils Schäfer (Credit and Capital Markets – Kredit und Kapital, 2021)
Considering the institutional factors of the German mutual fund market, we analyze equity fund holdings of German retail clients who received financial advice between 2005 and 2014 to investigate whether those investors overweight the bank-affiliated asset manager and if so, whether this bank-affiliated asset manager bias leads to higher fees, i.?e. Total Expense Ratios. Our analysis clearly indicates the presence of large bank-affiliated asset management biases for clients of all different banking sectors. Thus, German retail clients follow the biased financial advice they receive from their bank. Surprisingly, this bank-affiliated asset manager bias significantly reduces portfolio costs measured via mutual fund fees. Therefore, German banks disproportionately promote products of bank-affiliated asset managers but this biased advice does not lead to higher portfolio costs.
Keywords: G11; G23; G51; 330; Financial Advice; Mutual Investment Funds; Asset Management; Firm Bias; Management Fees